2020
DOI: 10.1186/s13006-020-00332-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of donor human milk on the length of hospital stay in very low birthweight infants: a systematic review and meta-analysis

Abstract: Background Donor human milk (DHM) is an alternative to preterm infant formula if the mother’s own milk is not available. Since the lactation period and preservation treatment of DHM are different from those of mother’s own milk, we aimed to determine the reduction in the length of hospital stay by DHM compared to preterm infant formula. Methods In this systematic review, we searched PubMed/MEDLINE, EMBASE, and the Cochrane Library to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Silano et al’s meta‐analysis of four RCTs, which comprised 953 subjects, found that donor human milk did not exert a clear protective effect on surgical NEC when it was compared with formula (RR: 0.45, 95% CI: 0.19–1.09) 9 . Yang et al 10 performed a meta‐analysis of 4 RCTs and 8 observational studies, with a total of 3221 subjects. Donor human milk had no impact on the length of hospital stay, compared with preterm formula, but it generally halved the incidence of NEC and the high‐quality RCTs reported an overall reduction of 68% 10 …”
Section: Does It Provide Vlbw Infants With Significant Health Benefits?mentioning
confidence: 99%
See 3 more Smart Citations
“…Silano et al’s meta‐analysis of four RCTs, which comprised 953 subjects, found that donor human milk did not exert a clear protective effect on surgical NEC when it was compared with formula (RR: 0.45, 95% CI: 0.19–1.09) 9 . Yang et al 10 performed a meta‐analysis of 4 RCTs and 8 observational studies, with a total of 3221 subjects. Donor human milk had no impact on the length of hospital stay, compared with preterm formula, but it generally halved the incidence of NEC and the high‐quality RCTs reported an overall reduction of 68% 10 …”
Section: Does It Provide Vlbw Infants With Significant Health Benefits?mentioning
confidence: 99%
“…Yang et al 10 performed a meta‐analysis of 4 RCTs and 8 observational studies, with a total of 3221 subjects. Donor human milk had no impact on the length of hospital stay, compared with preterm formula, but it generally halved the incidence of NEC and the high‐quality RCTs reported an overall reduction of 68% 10 …”
Section: Does It Provide Vlbw Infants With Significant Health Benefits?mentioning
confidence: 99%
See 2 more Smart Citations
“…In past decades there has been a resurgence in the establishment of donor milk banks in an effort to provide HM for vulnerable infants [ 285 ]. Donor milk has been shown to have positive effects of infant mortality and morbidity [ 286 ] whilst being economically cost effective [ 287 ]. We have been active in the formulation of best practice in milk banking which varies according to geography and resources [ 288 ] as well as investigating pasteurization methods.…”
Section: Donor Human Milkmentioning
confidence: 99%